Individual and additive-effect relationships of sleep problems and severe menopausal symptoms among women in menopausal transition. Issue 5 (May 2021) - Li, Yuanyuan; Zhao, Di; Lv, Gaorong; Mao, Cui; Zhang, Yunxue; Xie, Zihui; Li, Ping
Abstract: Objective: Sleep problems and menopausal symptoms are both common complaints among midlife women. However, the associations of the quality and quantity of sleep problems with the severity of menopausal symptoms have not been well studied. Thus, this study aims to examine the relationships between individual sleep problems and the additive number of sleep problems with severe menopausal symptoms among women during the menopausal transition. Methods: Using the convenience sampling, a total of 848 middle-aged women in China were investigated from December 2017 to August 2018. All participants completed a questionnaire on sleep problems, Menopause Rating Scale, and the general information questionnaire. Based on the cutoff of the Menopause Rating Scale, participants were divided into the nonsevere menopausal symptom group and severe menopausal symptoms group. Propensity score matching was used to balance covariates between the two groups. Stepwise binary logistic regression and restricted cubic spline were applied to analyze the associations of individual and additive sleep problems with severe menopausal symptoms. Results: After propensity score matching, no significant difference was observed between the nonsevere menopausal symptoms group and severe menopausal symptoms group ( P s > 0.05). Logistic regression analysis showed that five sleep problems ("feeling too hot, " "having pain, " "restless legs syndrome, " "taking medicine to help sleep, " and "having trouble staying awake") were closely associated with severe menopausal symptoms. The restricted cubic spline curve showed an upward trend in odds ratios between the number of these five sleep problems and severe menopausal symptoms, and women were more than twice as likely to suffer severe menopausal symptoms when they experienced more than three of these individual sleep problems. Conclusion: Both the individual and additive number of sleep problems exerted significant effects on severe menopausal symptoms. It might be useful for healthcare providers to set guidelines to support a healthy menopausal transition for midlife women. Abstract : Supplemental Digital Content is available in the text